Explanations for 10 of the most puzzling aspects of multisystem inflammatory syndrome and other Kawasaki‐like diseases. (2nd November 2021) - Roe, Kevin
Abstract: What is Known and Objective: An extensively documented multisystem inflammatory syndrome (MIS) has been observed in a small but significant percentage of COVID‐19 patients, in some adults but primarily in paediatric patients, and for these patients it is sometimes called MIS‐C. Comment: Kawasaki disease has also been observed over the last several decades in patients that tested positive for a variety of very virulent pathogens. Several differences and similarities between MIS‐C and Kawasaki disease pathology have been observed. Several puzzling aspects of MIS‐C, Kawasaki disease and other Kawasaki‐like diseases have been discussed, but not yet explained. What is New and Conclusion: An explanatory hypothesis has been presented. Using the hypothesis that a transient or permanent inability to quickly phagocytize antigen‐antibody immune complexes created by a novel virulent pathogen infection induces a Type III hypersensitivity immune response and the resulting proteinase exposure and expression of new autoantigens are the fundamental steps for MIS and other Kawasaki‐like diseases, it is possible to provide straightforward explanations for at least 10 of the most puzzling aspects of these diseases. The validity of the hypothesis itself is also supported by its ability to provide consistent and straightforward explanations for a large number of these disease aspects. Furthermore, these straightforward explanations and the explanatory hypothesis on which they are based also suggest several potential new treatments, which could possibly be more effective than various treatments in current use. Abstract : Using an explanatory hypothesis, it is possible to provide consistent and relatively straightforward explanations for 10 of the most puzzling aspects of Kawasaki disease, multisystem inflammatory syndrome (MIS), and the other Kawasaki‐like diseases.